A covalent organic framework as a photocatalyst for atom transfer radical polymerization under white light irradiation. Issue 2 (6th January 2021) - Lu, Zhen; Fu, Xiaoling; Yang, Hongjie; Zhao, Yulai; Xiao, Longqiang; Hou, Linxi
Abstract : TFPPy-Td-COFs have been synthesized to serve as heterogeneous photocatalysts for mediating photo-induced ATRP with copper as a co-catalyst under white light irradiation. Abstract : An imine-based covalent organic framework, TFPPy-Td-COF, was synthesized to mediate photo-induced controlled radical polymerization (CRP) with copper under white light irradiation, providing polymethylacrylates with narrow molecular weight dispersity and high chain-end fidelity. This new methodology provides future directions for CRP using robust and heterogeneous COF-based catalysts under visible light conditions.